Evaluating the effect of non-Newtonian turbulent blood models within a double-stenosed artery - Mohammed Ghalib Al-Azawy (Wasit Journal of Engineering Sciences)
This article describes the numerical investigation of blood rheology within an artery that includes two narrowing areas via Computational Fluid Dynamics (CFD). Elliptic blending Reynolds stress model and two models of viscosity have been used in this investigation utilizing STAR-CCM+ 2021.2.1. The test model includes two elliptical stenosis with a 2mm distance between them, and the area of stenosis is 75%. Results of normalized axial velocity, turbulent kinetic energy (TKE) and turbulent viscosity ratio (TVR) were evaluated before, through and after the stenosis in order to predict and avoid the real problems that occur from changing the area of the artery. Furthermore, Fractional flow reserve (FFR) was employed to assess the level of risk of stenosis through the artery, which depends on pressure measurements. Corresponding to the author's observation, it was found that the recirculation regions in the area between the stenosis are larger than the area after the stenosis. Moreover, the results of TKE and TVR are almost identical through and downstream of the stenosis, whereas the TKE is slightly higher with the Carreau model than with the Newtonian flow at the upstream and through the first stenosis.